Effects of production systems and ozone treatment on nitrate content and E. coli 0157H7 contaminations of Butterhead lettuce - Siti Fairuz Yusoff (Tanjong Malim, 2013)
Effects of production systems and ozone treatment on nitrate content and E. coli 0157H7 contaminations of Butterhead lettuce by Siti Fairuz Yusoff